A Theoretical Model of the Gasification Rate of Biomass and Its Experimental Confirmation - Savelii Kukharets; Gennadii Golub; Marek Wrobel; Olena Sukmaniuk; Krzysztof Mudryk; Taras Hutsol; Algirdas Jasinskas; Marcin Jewiarz; Jonas Cesna; Iryna Horetska (Energies, 2022)
The gasification rate of fuel, biomass gasification in particular, is an important parameter which is worth considering in the process of creating a gasifier with a continuous operation process. The gasification of biomass is a complex thermochemical process. The theoretical and practical studies of the gasification rate of biomass are complicated because of a high thermochemical rate of reactions in the functioning zones of a gasifier. The complexity of the study prevents the achievement of the required accuracy of the analytical model of the gasification rate of biomass. The known theoretical models of the gasification rate only partially describe the dynamics of the gasification rate of biomass. Moreover, most scientific studies are focused on establishing the effects of gasifier parameters and the gasification process on the quality indicators of the received gas but not on the gasification rate of fuel. To build an accurate model of the gasification rate the authors propose a series of experimental studies in a well-defined range of the parameters of a gasifier. The paper suggests a simple mathematical model of the gasification rate of biomass, which is proportional to the amount of plant biomass that remained non-gasified. The coefficients of the gasification rate for straw pellets, wood pellets and wood in pieces have been determined. Under a minimal air supply into an active zone of a gasifier (0.00088 m3/s) a coefficient of gasification rate is nearly the same for the test fuel materials and it differs by 4.7% between wood pellets and straw pellets. When the air supply increases, the gap between the coefficients increases as well and it reaches 9.44 × 10−5 c−1 for wood pellets, 1.05 × 10−4 c−1 for straw pellets and 8.64 × 10−5 c−1 for wood in pieces under air supply into an active zone of a gas generator of 0.01169 m3/s. Straw pellets have the highest gasification rate and wood in pieces has the lowest gasification rate.